2005
DOI: 10.1038/sj.bmt.1704942
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity allogeneic stem cell transplantation in relapsed and refractory Hodgkin's disease: low transplant-related mortality and impact of intensity of conditioning regimen

Abstract: Summary:A total of 40 patients with relapsed/refractory Hodgkin's disease (HD) underwent reduced-intensity conditioning (RIC) allogeneic stem cell transplantation (allo-SCT) from an HLA-identical sibling (n ¼ 20) or a matched unrelated donor (n ¼ 20). The median age was 31 years (range 18-58). Disease status at allo-SCT was refractory relapse (n ¼ 14) or sensitive relapse (n ¼ 26). The conditioning regimens were fludarabine-cyclophosphamide7antithymocyte globulin (n ¼ 14), a less intensive regimen, and fludara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 21 publications
7
79
3
1
Order By: Relevance
“…Such patients with positive uptake may need more innovative approaches. 24 Moscowitz et al 10 identified 3 factors before initiating cytoreductive chemotherapy that can predict outcome, including presence of B-symptoms, extranodal disease, and complete remission duration of less than 1 year. In our study, the presence of Bsymptoms and lack of CR/CRu at ASCT were independently predictive of PFS along with BEAM as the conditioning choice and FI results, whereas CR/CRu, radiation therapy, and BEAM were independently predictive for OS.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients with positive uptake may need more innovative approaches. 24 Moscowitz et al 10 identified 3 factors before initiating cytoreductive chemotherapy that can predict outcome, including presence of B-symptoms, extranodal disease, and complete remission duration of less than 1 year. In our study, the presence of Bsymptoms and lack of CR/CRu at ASCT were independently predictive of PFS along with BEAM as the conditioning choice and FI results, whereas CR/CRu, radiation therapy, and BEAM were independently predictive for OS.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 The first report, describing some of the best outcome data reported to date and also with long follow-up, included 20 consecutive NHL patients (10 patients with diffuse large cell lymphoma, 5 with mantle cell lymphoma and 5 with follicular lymphoma). 57 Patients were required to have stable or chemosensitive disease in order to be eligible to undergo allo-SCT.…”
Section: Non-myeloablative or Ric Allo-hsctmentioning
confidence: 99%
“…58 They used two conditioning regimens, fludarabine-CY with or without ATG, or a more intensive fludarabine and melphalan combination; GVHD prophylaxis consisted only of tacrolimus. Day 100 and 18-month cumulative TRM were 5 and 22%, respectively.…”
Section: Non-myeloablative or Ric Allo-hsctmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 With the advent of reduced-intensity conditioning regimens, there has been renewed interest in allogeneic transplantation in poor-risk patients with HL. 6,7 We previously reported a series of reduced-intensity allogeneic transplant (RIT), where a proportion of patients had failed a previous autograft. This showed encouraging estimated overall survival (OS) of 56% at 4 years with 2-year NRM of 16%.…”
Section: Introductionmentioning
confidence: 99%